Short stories for Japanese learners : learn Japanese with an authentic and fun short story collection for beginners. Volume 1 - Nishino, Yumi; Niimi, Nankichi, 1913-1943; Ogawa, Mimei, 1882-1961 (You can read Japanese! ;, 2023)
"Suitable for new learners who have learned Hiragana and Katakana and are able to read short sentences in simple grammar."